Caracterização edáfica e produção de Caesalpinia spinosa nos Andes Peruanos - Murga Orrillo, Hipolito (2022)
Tara (Caesalpinia spinosa) is a tree native to the South American Tropical Andes that, in the recent past, was neglected and suffered from the deforestation of natural forests, which were converted for agricultural and livestock production. Only more recently this species has gained notoriety, due to the fact that its pods have several components of commercial interest such as tannins and gum. Currently, Tara can be found in natural remnants or integrated into agroforestry systems, distributed along an altitudinal gradient with great edaphoclimatic variability. It is not known, however, which of these environmental conditions favor plant growth and pod production, which is a relevant field of study that can contribute to the adoption of production and management techniques suitable for commercial production. The objective of this work was to determine the influence of soil and climate conditions on plant density, pod, tannin and gum production. Data analysis of soil physicochemical attributes, dendrometry and plant production components followed four approaches: (a) an exploratory analysis of principal components (PCA) having as factors the environments (natural and agroforestry crops) and altitude classes (established according to a 1.0°C reduction in temperature with an increase in altitude) to verify possible groupings of the levels of the factors analyzed; (b) the identification of which variables were decisive to define the groupings observed in the PCA analysis through the evaluation of possible differences in the variables measured between the levels of the analyzed factors, using the bootstrap method to calculate the means and confidence intervals non-parametric parameters and (c) regression analysis of the variables of production components as a function of ambient temperatures and (d) correlation analysis between dendrometric data (plant density, plant and crown height, diameter). In the altitudinal gradient from 2021 to 3007±72 m, the temperature ranged from 19.8 to 13.44±0.37°C; the soils presented alkaline pH, high organic matter (OM), K and CTC, varied contents of CaCO3, N, P, K, B, Cu, Fe, Mn and Zn, in both environments and throughout the altitudinal gradient. The soil properties with the greatest contribution to PCAs were MO, CTC, N and sand, with no variation between environments, but between altitudes. All dendrometric variables did not vary as a function of altitude and temperature in PCAs run in a natural environment; but in the agroforestry environment it presented greater crown diameter, tree height and crown in the altitude class 2185 m associated with Medicago sativa, opposite behavior presented these variables in the altitude class 2798 m associated with low Fe contents, already in the altitude class 3007 m I have a larger trunk diameter associated with the highest levels of CaCO3. It was found that the weights of pods, valves, seeds and gum were higher in altitude classes 2798 and 3007 m in relation to lower altitude classes. For each 1°C increase in temperature, the length and width of the pod decrease by 2.1 and 0.62 mm, and of the seed by 0.17 and 0.12 mm in the agroforestry environment; likewise, pod, valve, seed and gum weights were reduced by 23.9; 10.9; 13 and 2.3 g in the agroforestry environment, and 22.3; 13; 9.3 and 2.1 g in the natural environment. The anthropic effect on the environment did not significantly alter the CTC, MO, N and sand. The crown diameter, crown height and tree height of Tara were higher in agroforestry environments. The variations of Fe, Mn, Zn and CaCO3 in the soil have evidence of influence on the development of Tara individuals in natural and agroforestry environments. Anthropogenic activities increase the length and width of the pod and seed, and the weight of the pod, valve, seed and gum in the agroforestry environment when compared to the natural one. Larger pod and seed dimensions, and higher pod, valve, seed and gum weights are related to higher soil CaCO3 contents in the natural environment and higher soil P and B contents in the agroforestry environment at higher altitudes. Higher Fe contents in the soil indicate an improvement in the tannin weight (valve) of Tara in the natural and agroforestry environment. In view of the above, it is important to emphasize that further studies on the production of Tara pods are necessary for a better understanding of the interaction with CaCO3, P, B and Fe in the soil.